Analisis Permukaan Baja ST 42 dalam Pengaruh Variasi Kecepatan Spindel dan Kedalaman Pemotongan pada Kekasaran Hasil Teknologi Pemesinan - Chendri Johan; Alfendi Ranteallo; Yafet Bontong; Sallolo Suluh; Pineng, Martina (Universitas Medan Area, 2025)
Surface roughness is an important aspect in machining that affects the appearance and function of the product. This study examines the effect of spindle speed and depth of cut on the surface roughness of ST 42 steel using HSS tools. Workpieces with a length of 300 mm and a diameter of 25 mm were processed with variations in spindle speed of 250, 350, and 450 rpm and depths of cut of 0.6, 0.7, and 0.8 mm. Roughness measurements were carried out using a surface tester. The results showed that at 250 rpm, the surface roughness was 0.0554 μm, at 350 rpm, 0.0517 μm, and at 450 rpm, 0.0416 μm. For the depth of cut, the roughness values were 0.0509 μm (0.6 mm), 0.0523 μm (0.7 mm), and 0.0542 μm (0.8 mm), respectively. The conclusion shows that increasing spindle speed reduces surface roughness, while depth of cut has a less significant effect.